An accurate and efficient three‐dimensional high order finite element methodology for the simulation of magneto‐mechanical coupling in MRI scanners - Paul Ledger (International Journal for Numerical Methods in Engineering, 2019)
Transient magnetic fields are generated by the gradient coils in an MRI scanner and induce eddy currents in their conducting components, which lead to vibrations, imaging artefacts, noise and the dissipation of heat. Heat dissipation can boil off the helium used to cool the super conducting magnets and, if left unchecked, will lead to a magnet quench. Understanding the mechanisms involved in the generation of these vibrations, and the heat being deposited in the cryostat, are key for a successful MRI scanner design. This requires the solution of a coupled physics magneto‐mechanical problem, which will be addressed in this work. A novel computational methodology is proposed for the accurate simulation of the magneto‐mechanical problem using a Lagrangian approach, which with a particular choice of linearisation leads to a staggered scheme. This is discretised by high order finite elements leading to accurate solutions. We demonstrate the success of our scheme by applying it to realistic MRI scanner configurations.